Android-Based Studend Cooperative Application (Case Study of Kopma UMK) - Agung Prasetyo; Ghozali, Muhammad Imam; Sugihartono, Wibowo Harry (Jurnal Teknologi Informasi dan Pendidikan, 2025)
Many cooperatives in Indonesia still rely on manual systems, resulting in slow processes, inefficiency, and data inconsistencies. To address this issue, an Android-based KOPMA application was developed using the Dart programming language and Flutter framework. The system facilitates management of member data, sales transactions, and savings in a more effective way. Implementation at KOPMA Universitas Muria Kudus demonstrated faster services, reduced data errors, and improved work effectiveness, while also contributing to student entrepreneurship through a modern and integrated system.